البعد الجمالي للحكي في شعر تميم البرغوثي "في القدس أنموذجا" - اوراغ, بلقاسم (جامعة الوادي - University of Eloued, 2021)
ملخص: يسعى هذا البحث إلى الإفادة من العلاقة بين الأديب والأحداث التي تجعله يقوم بسردها،و التواصل معها بطرق مختلفة و أصول متعددة، وهذا ما عرف بالحكي، فمنذ القديم تناقلت الإنسانية أخبارها وأحداثها بطرق مختلفة ومتنوعة وخاصة الشعر ؛ بدءا بالوقوف على الأطلال في العصر الجاهلي وصولا إلى الشكل المعاصر للقصيدة الشعرية، ومن النماذج الشعرية التي يحتفي بها الشعر العربي المعاصر أشعار "تميم البرغوثي"، التي احتوت في ثناياها الكثير من الخصائص الجمالية التي شكلت أساس الحكي في قصائده، وبناءا على ذلك سوف تحاول هذه الدراسة الوقوف على أهم العلاقات والتفاعلات التي تحدث في نفسية الشاعر من خلال استجلاء أهم آليات الحكي الموجودة في القصيدة، والمتمثلة في:المكان، الزمن، الشخصيات. الكلمات المفتاحية: الحكي، الزمن ، المكان، الشخصيات، القدس. Abstract: This research seeks to benefit from the relationship between the writer and the events that make him narrate them, and communicate with them in different ways and have multiple origins, and this is what was known as narration, since ancient humanity has transmitted its news and events in different and varied ways, especially poetry، From standing on the ruins of the pre-Islamic era to the contemporary form of the poem. Among the poetic models celebrated by contemporary Arabic poetry is the poetry of Tamim Al-Barghouti, which contained many aesthetic characteristics that formed the basis of narration in his poems. Accordingly, this study will try to identify the most important relationships and interactions that occur in the psyche of the poet by exploring the most important mechanisms of narration present in the poem, which are: the place; Time; Personalities. key words: Storytelling Time, the place, Characters, Jerusalem.
مقال
Keywords: الحكي ; الزمن ; المكان ; الشخصية ; القدس